2023
DOI: 10.1007/s42417-023-00906-8
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Temperature-Dependent Resonance Behavior of Ultrasonic Transducers Using the Finite-Element Method

Abstract: Purpose Langevin transducers are ultrasonic transducers that convert electrical into mechanical energy through the piezoelectric effect. This class of transducers achieves the highest efficiency in their mechanical resonance. Studies have shown that the resonant frequency changes with temperature. The aim of this contribution is to reproduce this temperature-dependence resonance frequency as accurately as possible with FEM simulations. Methods Therefore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…159 Studies have shown that ultrasonic vibrations tend to attenuate more with an increase in distance, 160 an increase in the density of medium, 161 and an increase in the temperature. 162,163 Therefore, when dealing with refractory powders that have high density and require high processing temperatures, it is crucial to conduct an in-depth analysis of the attenuation of ultrasonic vibrations used to aid the AM process.…”
Section: Future Trendsmentioning
confidence: 99%
“…159 Studies have shown that ultrasonic vibrations tend to attenuate more with an increase in distance, 160 an increase in the density of medium, 161 and an increase in the temperature. 162,163 Therefore, when dealing with refractory powders that have high density and require high processing temperatures, it is crucial to conduct an in-depth analysis of the attenuation of ultrasonic vibrations used to aid the AM process.…”
Section: Future Trendsmentioning
confidence: 99%